Analytical and Numerical Study of the Ground Pressure of the Work Face Crossing the Fault - Yanan Gao; Yudong Zhang; Donghao Lan; Feng Gao (Advances in Materials Science and Engineering)
The excavation of coal mine often encounters the fault problem. In this paper, the analytical study of the pressure of the fault that the work face may cross is carried out. The evolution of the stress and moment of the fault is investigated. Afterwards, a numerical study is performed. The stress and displacement of the rock mass near the work face and the fault are calculated under each situation (the initial fracture and periodical fracture of the immediate roof, the forward direction fault, and the reverse direction fault), and the changes in the contact pressure and stress near the fault during the excavation are analyzed. The effect of searching tunnel on the mining pressure is also studied. The calculation results indicate that although the searching-tunnel can decrease the stress at the roof of the fault (reverse direction fault), it may increase the stress at other positions. It can therefore be concluded that, for the forward direction fault, the effect of the searching tunnel to decrease the contact pressure and dissipate the energy is limited; on the contrary, it will aggravate the fragmentation degree and make the support more difficult, while, for the reverse direction fault, the excavation of searching tunnel can not only provide a better understanding of the characters of the fault but also have a positive effect on the ground control.